2014
DOI: 10.1039/c4tb01409j
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecule detection in porous silicon based microcavitiesviaeuropium luminescence enhancement

Abstract: The ability of a porous silicon microcavity (pSiMC) to act as a luminescence enhancing sensor was confirmed using Eu(iii) complex labelled streptavidin as a model analyte on a biotin-modified pSiMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…The resulting 1D photonic structures exhibit a photonic band gap with preventing light reflectance at certain wavelengths. The range of possible 1D pSi photonic crystals include Bragg reflectors, microcavities, and rugate filters 127b. In addition, pSi can be engineered to couple and guide light, rendering resonant structures such as waveguides, resonant rings, and Bloch surface waves …”
Section: Psi‐based Biosensorsmentioning
confidence: 98%
See 1 more Smart Citation
“…The resulting 1D photonic structures exhibit a photonic band gap with preventing light reflectance at certain wavelengths. The range of possible 1D pSi photonic crystals include Bragg reflectors, microcavities, and rugate filters 127b. In addition, pSi can be engineered to couple and guide light, rendering resonant structures such as waveguides, resonant rings, and Bloch surface waves …”
Section: Psi‐based Biosensorsmentioning
confidence: 98%
“…In addition, when the product of an enzymatic reaction is the generation or quenching of luminescence, photonic microcavities can be used to enhance this signal and significantly improve the biosensor sensitivity. Recently, Voelcker and his group established a few biosensors focused on the fluorescent enhancement induced by pSi resonant structures . This attribute has been exploited to develop ultra‐sensitive biosensors.…”
Section: Psi‐based Biosensorsmentioning
confidence: 99%
“…Porous silicon (PSi)-based nanostructures have been widely reported as potential host matrices for light emitting materials, including organic dyes (Palestino et al, 2008 ; Jenie et al, 2014 , 2015 ; Krismastuti et al, 2014 ; Mo et al, 2017 ) and quantum dots (QDs) (DeLouise Lisa and Ouyang, 2009 ; Qiao et al, 2010 ; Gaur et al, 2011 , 2013 ; Dovzhenko et al, 2015 , 2018a ; Liu et al, 2015 ; Dovzhenko D. S. et al, 2016 ; Li et al, 2017 ; Zhang et al, 2017 ). PSi-based photonic crystals hosts [e.g., Bragg reflector (Liu et al, 2015 ; He et al, 2017 ; Li et al, 2017 ) and microcavities (Jenie et al, 2014 , 2015 )] have been shown to affect the propagation and distribution of the light emitted by the guest fluorophores (Pacholski, 2013 ; Dovzhenko D. et al, 2016 ; Dovzhenko D. S. et al, 2016 ). Specifically, PSi-based microcavities have been shown to improve the spectral properties of emitting molecules, e.g., quantum yield, photostability and luminescence lifetime, by alignment between the reflectance spectrum dip of the microcavity and the emission of the fluorophores (Jenie et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the rate of mass transport from bulk solution to interface (infiltration rate) is significant for various research areas such as membrane separation, [1][2][3] interfacial chemical reaction, [4][5][6][7][8] thin film fabrication, [9][10][11][12] sensing, [13][14][15] etc. Taking the layer-by-layer assembled multilayer 9,10,[16][17][18][19][20][21] as an example, there is a paradox between increasing the loading amount and enhancing the infiltration rate because the multilayer should grow thick for high loading capacity; 22,23 this results in an increased barrier for infiltration through the multilayer, and thus, a decreased infiltration rate.…”
Section: Introductionmentioning
confidence: 99%